Mengabdi Bersama GenBI dalam Mengembangkan Desa Wisata yang Inovatif, Berwirausaha dan Mandiri - Baiq Candra Herawati; Suhendra, Erwin (Insan Kreasi Media, 2025)
This community engagement initiative by GenBI Universitas Bumigora focused on empowering Kebon Ayu Village, West Lombok, as an innovative and self-reliant tourism destination. Despite its rich cultural and natural assets, the village faced challenges such as limited digital literacy, underdeveloped entrepreneurship, and low community participation in tourism development. Utilizing the Asset-Based Community Development (ABCD) approach, the program emphasized leveraging existing local strengths through participatory methods. Activities included English language training for children, digital marketing workshops for local entrepreneurs, QRIS digital payment education, and community clean-up campaigns. These interventions led to increased community involvement, the emergence of local leaders, and enhanced digital and entrepreneurial skills among residents. The outcomes align with empowerment theory, highlighting that access to resources, skills, and supportive social structures enables communities to achieve collective goals. This case underscores the effectiveness of participatory, asset-based strategies in fostering sustainable rural tourism development and community empowerment.